PENGARUH MEDIA AUDIO-VISUAL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) - Farina Sari; Arwin Achmad; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Critical thinking skills and mastery of subject matter is required by students in the learning procces. The research has purpose to determine the effect of application audio-visual media through TPS model to the critical thinking ability and material mastery on environmental management subject matter. This is a experimental study research by pretest postest non equivalent group design. The samples of this research are VII E and VII F classroom chosen by purposive sampling method. Quantitative data obtained from the pretest and the posttest which analyzed statistically using t-test by spss 17. Qualitative data obtained from questionnaire regarding student response on audio-visual media through TPS model which analyzed descriptively. The results showed an increase in the critical thinking skills and material mastery of the experimental class on all indicators (critical thinking skills N-gain 61.12%, mastery of subject matter N- gain 62.25%). Moreover, 70% students give positive response on audio-visual media through TPS learning model. Therefore, the using of audio-visual media through TPS has influence significantly to increasing the critical thinking skill and material mastery of the student. Keywords: audio-visual media, cooperative learning model of TPS,   critical thinking skill, material mastery.